2006
DOI: 10.1088/0963-0252/15/2/s14
|View full text |Cite
|
Sign up to set email alerts
|

The multiscale nature of streamers

Abstract: Streamers are a generic mode of electric breakdown of large gas volumes. They play a role in the initial stages of sparks and lightning, in technical corona reactors and in high altitude sprite discharges above thunderclouds. Streamers are characterized by a self-generated field enhancement at the head of the growing discharge channel. We briefly review recent streamer experiments and sprite observations. Then we sketch our recent work on computations of growing and branching streamers, we discuss concepts and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
277
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(291 citation statements)
references
References 74 publications
13
277
1
Order By: Relevance
“…First, fully three-dimensional simulations are required to follow streamer evolution after branching. We actually expect the branching time in cylindrical symmetry to be a close upper bound for the actual branching time in the fully three-dimensional situation [48,20]. Second, numerical solutions of our deterministic fluid model show that it is actually admissible for streamer propagation to neglect densities below the threshold of 1 particle per mm 3 where the continuum approximation definitely ceases to hold; we have used this threshold on our computations with refinement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, fully three-dimensional simulations are required to follow streamer evolution after branching. We actually expect the branching time in cylindrical symmetry to be a close upper bound for the actual branching time in the fully three-dimensional situation [48,20]. Second, numerical solutions of our deterministic fluid model show that it is actually admissible for streamer propagation to neglect densities below the threshold of 1 particle per mm 3 where the continuum approximation definitely ceases to hold; we have used this threshold on our computations with refinement.…”
Section: Discussionmentioning
confidence: 99%
“…For the advection part we get a Courant-Friedrichs-Lewy (CFL) restriction 20) and the diffusion part leads to…”
Section: Temporal Discretizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron-neutral collisions, including all relevant elastic, excitation, and ionization collisions, are treated with the Monte Carlo method. Electron-electron or electron-ion processes as well as density changes of the neutral gas are neglected as the degree of ionization stays below 10 −5 even at atmospheric pressure [18,27]. This well-known model will be summarized in section II A.…”
Section: Set-up Of Particle Model and Fluid Model In Local Field mentioning
confidence: 99%
“…Another recent result supporting the fluid approximation for streamers was that even streamer branching [25,26,27] can be understood in terms of an inherent instability of the fully deterministic fluid equations [19,27,28,29,30]. These studies have shown that a streamer in nitrogen can reach a state in which the width of the space charge layer that creates the field enhancement at the streamer tip, is much smaller than the streamer diameters; the streamer then can branch spontaneously due to a Laplacian interfacial instability.…”
Section: Introductionmentioning
confidence: 96%